Identification of novel Lck‐derived T helper epitope long peptides applicable for HLA‐A2+ cancer patients as cancer vaccine. Issue 11 (16th October 2015) - Matsueda, Satoko; Shichijo, Shigeki; Nagata, Sayaka; Seki, Chieko; Yamada, Akira; Noguchi, Masanori; Itoh, Kyogo
Abstract : The present study attempted to identify T helper epitope long peptides capable of inducing cytotoxic T lymphocytes (CTL) from Lck antigen (p56 Lck ), the src family tyrosine kinase, which is known to be aberrantly expressed in metastatic cancers cells, in order to develop a long peptide‐based cancer vaccine for HLA‐A2 + cancer patients. Based on the biding motif to the HLA‐DR and HLA‐A2 alleles, 94 peptides were prepared from the Lck antigen. These peptides were screened for their reactivity to immunoglobulin G (IgG) from plasma of cancer patients, followed by testing of their ability to induce both CD4 + and CD8 + T lymphocytes showing not only peptide‐specific IFN‐γ production but cytotoxicity against HLA‐A2 + cancer cells from peripheral blood mononuclear cells (PBMC) of HLA‐A2 + cancer patients. Among 94 peptides tested, the three T helper epitope long peptides and their inner CTL epitope short peptides with HLA‐A2 binding motifs were frequently recognized by IgG of cancer patients, and efficiently induced both CD4 + IFN‐γ + and CD8 + IFN‐γ + T lymphocytes. Patients' PBMC stimulated with these long peptides showed cytotoxicity against HLA‐A2 + Lck + cancer cells in HLA‐class I and HLA‐class II dependent manners. These three peptides might be useful for long peptide‐based vaccines for HLA‐A2 + cancer patients with Lck + tumor cells. Abstract : Among 94 peptides tested, the three T‐helper epitope long peptides and their inner CTL epitope short peptides with HLA‐A2 binding motifs were frequently recognized by IgG of cancer patients, and efficiently induced both CD4 + IFN‐γ + and CD8 + IFN‐γ + T lymphocytes.